INCREASE RESILIENCY ALGORITHM OF PROGRAM COMPONENTS INTEGRATION BASED ON CORBA TECHNOLOGY - Eduard I. Yambulatov (Вестник Северо-Кавказского федерального университета, 2022)
In the article the algorithm, which allows to increase the availability and minimize the response time to failure of the integration process in the management of telecommunications technology based CORBA is proposed.